MEASURING THE STUDENTS' LEARNING ACHIEVEMENT AT THE HEALTH AND RECREATION PHYSICAL EDUCATION STUDY PROGRAM DURING ONLINE LEARNING - Nuryati Nuryati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This research was evaluation research aiming to determine the students' learning achievement during the online learning period. The research subjects were the 5th-semester students of the SB Banten PJKR Study Program. The evaluation method used in this research was CIPP (Context, Input, Process, Product) evaluation. The study results indicated that the learning activities used a blended learning model, which combined online learning activities for the theory and face-to-face (offline) learning for practical activities. Judging from the condition of the campus, it had adequate facilities. The infrastructure or the media for the learning process was quite complete. Then, the institution had comfortable classrooms, multipurpose fields, and adequate equipment. The curriculum followed the KKNI. However, the activities were not optimal due to the pandemic conditions that limited the number of students in each meeting. Only 50% of the total students were in one class. At the same time, the evaluation or assessment was carried out through practical activities following the subjects taught.